An assisted propulsion device of vessel utilizing wind energy based on Magnus effect. (September 2021) - Li, Boyang; Zhang, Rui; Zhang, Baoshou; Yang, Qianqian; Guo, Chao
Highlights: A new combination of the sail and a Flettner Rotor. The polygonal sail is simulated and calculated using CFD commercial code. The greater number of the sail sides, the greater the lift coefficient. The maximum propulsive power produced by the 16-sided sail is 2005 kW. The maximum thrust that the 16-sided sail can provide to the vessel is 540 kN. Abstract: This research proposes a new type of vessel assisted propulsion device, which is a polygonal sail composed of sails and cylinders, and the sail is essentially a super large Flettner rotor that can be deformed. The main structure of the device is modelled using SolidWorks software and a three-dimensional computational domain containing the polygonal sails is established to analyses the beneficial effects that the polygonal sails provide to the vessel. The polygonal sail is simulated and calculated using CFD commercial code under various working conditions. A comparative analysis of the lift coefficients and drag coefficients for nine groups shapes of polygonal sails, which found that the greater number of the sail sides, the greater the lift coefficient. After a comprehensive comparison, it is concluded that the 16-sided sail has better practical application value for a 300000-ton tanker. Further numerical simulations are operated for the model of 16-sided sail, and the maximum lift that the sail can provide to the vessel is 590 kN. When the spin ratio k is 1, 8-level wind conditions, the maximum propulsive power of the sail is 2005 kW. In addition, the Reynolds number is also one of the main factors affecting the force coefficient of a polygonal sail. As the Reynolds number increases, the lift-to-drag ratio of the sail becomes smaller.